The relationship of small vessel disease burden on cerebral and regional brain atrophy rates and cognitive performance over one year of follow-up after transient ischemic attack - Reaume, Noaah; Reid, Meaghan; Tadros, George S.; Chacinski, Dorothy; Denroche, Britney; Aftab, Arooj; Wu, Pauline; Gupta Sah, Rani; Wang, Meng; Smith, Eric E.; Frayne, Richard; Coutts, Shelagh B.; et al. (Frontiers in Neurology, 2023)
Background Stroke, even when minor, increases the risk of dementia. We aimed to determine whether patients with transient ischaemic attack (TIA) exhibit higher rates of cerebral and regional atrophy 1-year after first stroke symptoms and evaluate the relationship with small vessel disease and cognitive performance. Methods TIA patients and controls without cognitive symptoms underwent high-resolution T1-weighted MRI and cognitive testing at baseline and 1-year. Percent brain volume change (PBVC) was measured, and the location of regional atrophy and small vessel disease (CSVD) burden was evaluated. Neuropsychological testing assessed memory, processing speed, and executive function. Results A total of 76 TIA patients and 53 controls of mean age 67 (SD = 8) and 68 years (SD = 8) were recruited. TIA patients demonstrated greater improvement of visual memory and executive function at 1-year. TIA patients had greater median PBVC/year compared to controls (−0.79% [(−1.22)-(−0.38)] vs. -0.41% [(−0.62)-0.19]; p < 0.001), and higher rates of volume loss (ml/year) in subcortical gray (−0.53 [(−1.09)-(−0.06)] vs. -0.13 [(−0.61)-0.31]; p < 0.05) and white matter (−2.21 [−5.47, 0.40] vs. -0.93 [(−3.43)-2.10]; p < 0.05). Linear regression showed that TIA, age, and systolic blood pressure (SBP) were associated with greater cerebral volume loss over 1-year. There was no significant relationship between PBVC and 1-year cognition. Conclusion A near two-fold increase in rate of cerebral atrophy 1-year after TIA is associated with higher SBP emphasizing the need for improved treatment of SBP. Cerebral and regional atrophy rates may be used to select patients for vascular risk reduction trials or novel therapeutics in future dementia prevention trials.